2019
DOI: 10.1158/1541-7786.mcr-19-0545
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Signaling Can Modulate MHC Class I and II Expression

Abstract: Molecular events activating the PI3K pathway are frequently detected in human tumors and the activation of PI3K signaling alters numerous cellular processes including tumor cell proliferation, survival, and motility. More recent studies have highlighted the impact of PI3K signaling on the cellular response to interferons and other immunologic processes relevant to antitumor immunity. Given the ability of IFNg to regulate antigen processing and presentation and the pivotal role of MHC class I (MHCI) and II (MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…Of note, while PI3K and AKT1 inhibitors have also been shown to boost IFNG-driven class I and class II antigen presentation as a mechanism of cancer-cell-dependent immunostimulation (Chandrasekaran et al, 2019;Marijt et al, 2019;Sivaram et al, 2019), MTOR inhibitors are not expected to mediate a similar activity, largely reflecting the notions that these agents potently activate autophagy (Galluzzi et al, 2017a) and that autophagy limits MHC class I levels on the surface of malignant cells (Yamamoto et al, 2020). Moreover, autophagy is a potent inhibitor of type I IFN secretion by breast cancer cells responding to radiation (Rodriguez-Ruiz et al, 2019;Yamazaki et al, 2020), implying that caution should be taken when combining MTOR inhibitors with radiotherapy.…”
Section: Kras and Pi3k Signaling Inhibitorsmentioning
confidence: 99%
“…Of note, while PI3K and AKT1 inhibitors have also been shown to boost IFNG-driven class I and class II antigen presentation as a mechanism of cancer-cell-dependent immunostimulation (Chandrasekaran et al, 2019;Marijt et al, 2019;Sivaram et al, 2019), MTOR inhibitors are not expected to mediate a similar activity, largely reflecting the notions that these agents potently activate autophagy (Galluzzi et al, 2017a) and that autophagy limits MHC class I levels on the surface of malignant cells (Yamamoto et al, 2020). Moreover, autophagy is a potent inhibitor of type I IFN secretion by breast cancer cells responding to radiation (Rodriguez-Ruiz et al, 2019;Yamazaki et al, 2020), implying that caution should be taken when combining MTOR inhibitors with radiotherapy.…”
Section: Kras and Pi3k Signaling Inhibitorsmentioning
confidence: 99%
“…93 Pharmacological inhibition of PI3K restored IFNγ/STAT1 signaling transduction and surface class I HLA expression in vitro. 93 129 A study by Sivaram et al investigating the impact of mutational activation of PI3K in an orthotopic pancreas mouse model showed that inhibition of the PI3K pathway increases MHC-I expression, leading to tumor regression due to T cell infiltration. 130 Importantly TCGA database analysis also reveals a negative correlation between activated PI3K-Akt and HLA-I-mediated regression in head and neck cancer, lung squamous carcinoma, and pancreatic adenocarcinoma.…”
Section: Microenvironmental Regulation Of Hla Expressionmentioning
confidence: 99%
“…We have previously linked PI3K pathway signaling to tumor antigen presentation mechanisms in head and neck cancers. PTEN loss and PI3K activation downregulated major histocompatibility complex (MHC) Class I and Class II induction by IFN-g, and clinical tumor samples demonstrated inverse staining associations of MHC and Phospho-S6, a serine/ threonine kinase downstream of PI3K (106). Downregulation of MHC expression in HNSCC and melanoma has a clinical correlation with treatment resistance and poorer clinical outcomes (102)(103)(104).…”
Section: Pi3k-d and -G Effects In The Tmementioning
confidence: 99%